Fiscal Rules-Anchoring Expectations for Sustainable Public Finances. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
The sharp increase in fiscal deficits and public debt in most advanced and several developing economies has raised concerns about the sustainability of public finances and highlighted the need for a significant adjustment over the medium term. This paper assesses the usefulness of fiscal rules in supporting fiscal consolidation, discusses the design and implementation of rules based on a new data base spanning the whole Fund membership, and explores the fiscal framework that could be adopted as countries emerge from the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet